2003
DOI: 10.1096/fj.02-1102fje
|View full text |Cite
|
Sign up to set email alerts
|

The breakdown of pre‐existing advanced glycation end products is associated with reduced renal fibrosis in experimental diabetes

Abstract: Renal accumulation of advanced glycation end products (AGEs) has been linked to the progression of diabetic nephropathy. Cleavage of pre-formed AGEs within the kidney by a cross-link breaker, such as ALT-711, may confer renoprotection in diabetes. STZ diabetic rats were randomized into a) no treatment (D); b) treatment with the AGE cross-link breaker, ALT-711, weeks 16-32 (DALT early); and c) ALT-711, weeks 24-32 (DALT late). Treatment with ALT-711 resulted in a significant reduction in diabetes-induced serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
203
2
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 252 publications
(221 citation statements)
references
References 66 publications
14
203
2
2
Order By: Relevance
“…In our study, delayed intervention with alagebrium was associated with a significant attenuation of oxidative stress in the vascular wall, as measured by accumulation of nitrotyrosine residues. By contrast, it has previously been found that alagebrium, 10 mg kg −1 per day −1 , did not decrease renal nitrotyrosine staining in the kidney of diabetic rats when given as a delayed intervention [18].…”
Section: Discussionmentioning
confidence: 68%
“…In our study, delayed intervention with alagebrium was associated with a significant attenuation of oxidative stress in the vascular wall, as measured by accumulation of nitrotyrosine residues. By contrast, it has previously been found that alagebrium, 10 mg kg −1 per day −1 , did not decrease renal nitrotyrosine staining in the kidney of diabetic rats when given as a delayed intervention [18].…”
Section: Discussionmentioning
confidence: 68%
“…First, we used the putative AGE crosslink breaker alagebrium chloride (ALT-711) [26]. When AGE-modified apoA-I was pretreated with 0.1 mg/ml alagebrium chloride, its ability to support cholesterol efflux was fully restored (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Collagen-associated AGE fluorescence was determined in 24-h acid-hydrolysed collagen preparations following sequential extractions with 1.0 mol/l NaCl, 0.5 mol/l acetic acid and delipidation with chloroform:methanol (1:2) by flow injection, as described above [25]. To correct for differences in the collagen content of samples, fluorescence intensity was expressed as the percentage of fluorescence per mg renal collagen.…”
Section: Measurement Of Total Renal Collagen and Collagen-associated mentioning
confidence: 99%